The influence of the habit of consuming sour turmeric drinks on complaints of dysmenorrhea in adolescent at Pebayuran’s Senior High School - Septiwiyarsi, Septiwiyarsi; Iskandar, Marini; Suriyah, Melti (Journal of Midwifery and Nursing, 2024)
Adolescent girls are a group that is prone to experiencing dysmenorrhea. Dysmenorrhea can be treated with turmeric acid drink. Curcumine functions as an analgesic which inhibits excessive prostaglandin release, thereby inhibiting uterine contractions and reducing dysmenorrhea pain. Research objective: to determine the effect of sour turmeric drink on dysmenorrhea in young women. Type of pre-experimental research with one group pre-post test design. This research was conducted in March 2023 at SMA N 1 PEBAYURAN Bekasi Regency. The sampling technique was purposive sampling. The sample numbered 39 people. Results: The average value before being given the turmeric acid drink was 6.1760 and after being given the turmeric acid drink the mean value changed, namely 2.7345. The results of statistical tests on the group given the sour turmeric drink obtained a p value of 0.000, meaning that there was an effect of the sour turmeric drink on complaints of dysmenorrhoea in young women at SMA N 1 Pebayuran. It is hoped that health workers can educate young women regarding the management of dysmenorrhea by consuming turmeric acid drinks